Sustainable education for refugees children: a literature review - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Kyu, Kyu Win; Noviani, Wulan (IIUM Press, 2024)
This literature review describes the educational needs, challenges, and potential solutions for refugee children, aiming to provide insights into how to improve their access to quality education. Applying the PRISMA flow, a comprehensive search yielded 10 articles published between 2013 and 2023, which were analyzed to identify recurring themes. Three prominent themes emerged from the literature: challenges faced by refugee children and their teachers, access to quality education, and sustainable education initiatives for refugee children. The literature highlights the multifaceted obstacles encountered by refugee children, including displacement, trauma, language barriers, and limited access to educational resources. Moreover, teachers working with refugee children face unique challenges related to accommodating diverse cultural and linguistic backgrounds, addressing trauma and mental health needs, and navigating complex administrative and policy frameworks. Additionally, access to quality education remains a significant concern, with disparities persisting due to socioeconomic status, geographic location, and systemic inequalities. Sustainable education initiatives play a crucial role in addressing these challenges, emphasizing inclusivity, cultural sensitivity, and community engagement. Key components of sustainable education for refugee children include access to quality schooling, teacher training, psychosocial support, language acquisition, and pathways to higher education or vocational training. Therefore, this literature review underscores the urgent need for comprehensive and targeted interventions to address the educational needs of refugee children. Recommendations include investing in teacher training, fostering partnerships with local communities and organizations, advocating for policy reforms to promote inclusive education, and providing ongoing support for sustainable education initiatives. By addressing these challenges and implementing evidence-based strategies, stakeholders can work towards ensuring that refugee children receive the education they deserve, enabling them to build better futures for themselves and their communities.